KEPRAKTISAN MODEL ASSURANCE, RELEVANCE, INTEREST, ASSESSMENT, SATISFACTION (ARIAS) PADA PEMBELAJARAN MATEMATIKA - Neneng Aminah (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2016)
Mathematics is one of the basic subjects which is taught at every level of education, because it equips learners have the ability to think logically, analytically, systematicaly, critically and creatively, and the ability to solve problems and work together. In fact, many students do not have those abilities. One of the ways to improve their mathematical abilities is doing an effective learning with practical learning tools. In this study ARIAS learning model learning is as a tool of learning device. To achieve its practicality, learning devices are made to ease the teacher and student understanding. This study aimed to analyze the practicality of the learning device. This learning device is said to be practical if it has been tested in the experimental class and it gained positive response from students and teachers, and teacher has good interpretation when he manage his classroom activities. The result of this research is 79% of positive responses from teachers, and 87% positive responses from the students, and the average is 3.4 teachers manage the class well.